If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -10 + 12 = 180 Reorder the terms: -10 + 12 + 2x = 180 Combine like terms: -10 + 12 = 2 2 + 2x = 180 Solving 2 + 2x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2x = 180 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = 180 + -2 2x = 180 + -2 Combine like terms: 180 + -2 = 178 2x = 178 Divide each side by '2'. x = 89 Simplifying x = 89
| 11x-10+39+6x+11= | | 4x*x=5*20 | | 2(3x+1)+5(x-4)= | | 9x+8=6x+47 | | 2(p-3)+6=-10 | | g-11=7 | | 6k=6k+48 | | 7x-4=72 | | 2(33+11x+3x)=11*3*X | | sqrt((64b^27)/(27a^15)) | | 6n+8-4n=-20 | | 2(36+9x+4x)=9*4*x | | 118=g-4/2/5 | | 4x=x-8+20 | | -20=-3r-5 | | 7xyz^3-5y^2z^2+1=n | | 5x-2x=7x-2 | | 0.5z=6 | | 2x+8+9x=-80 | | n=2.125+-1.125n | | 3x-5x=8x+10 | | 100=15y+10y | | 0.20*-250+0.30=0.27*-250+25 | | 3-4x=6(2/3x-1/2) | | 5y=15-6x | | 4(r-3)+1=33 | | 5q+14=4 | | 13x+3+85+85+96=180 | | -1=d+21 | | 2(33+11x+3x)=c | | x^2+(-4x-14)(-4x-14)=25 | | (5q-2)+3-4q=4 |